2017
DOI: 10.18203/2394-6040.ijcmph20173151
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor assessment and screening for diabetes in field practice area of a private medical college in Thiruvallur district of Tamil Nadu

Abstract: Background: Diabetes, which was known to be an epidemic in the urban areas, has been found to be increasing rapidly in the rural areas too as a result of the socioeconomic transitions. Diabetes is no longer only a disease of the elderly but is one of the major causes of morbidity and mortality affecting youth and middle aged people.Methods: Screening camp for diabetes was conducted by the Department of Community Medicine in three different areas in the field practice area of Saveetha Medical College and Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…Although, the facility-based screening sample in this study could have led to selection bias, since only persons who signed consents to participate in the 4D project were scored using the FINDRISC tool. We also found that women accessed both screening methods more than men, and this is similar to other studies [ 66 , 67 ]. Also, women in general tend to be recruited to participate in intervention studies more often than men [ 68 ].…”
Section: Discussionsupporting
confidence: 91%
“…Although, the facility-based screening sample in this study could have led to selection bias, since only persons who signed consents to participate in the 4D project were scored using the FINDRISC tool. We also found that women accessed both screening methods more than men, and this is similar to other studies [ 66 , 67 ]. Also, women in general tend to be recruited to participate in intervention studies more often than men [ 68 ].…”
Section: Discussionsupporting
confidence: 91%
“… 9 A study was done in Thiruvallur district in Tamil Nadu in 2017 highlights a significant burden of undiagnosed cases of diabetes in the community and this indicates the need for systemic screening and awareness programs to identify the undiagnosed cases in the community and offer early lifestyle modification, treatment and regular follow up to such individuals. 10 A study was done by Deepthi et al showed that the prevalence of diabetes, IFG, and their risk factors are high among the rural population of Kolar indicating the impending diabetic epidemic in rural areas. Undiagnosed diabetes, which is a hidden danger, is high among rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…The Chennai Urban Population Survey [23] reported that the prevalence of diabetes was higher in subjects who had a positive family history (18.2%) as compared to those without (10.6%). Around 64.7% and 54.2% of the study participants had a family history of diabetes in studies conducted by Dev et al [24] and Valliyot et al [25], respectively.…”
Section: Shrabani Et Almentioning
confidence: 99%